Low Levels Matter: Clinical Relevance of Low Pru p 3 sIgE in Patients With Peach Allergy - Balsells-Vives, Sara; San Bartolomé, Clara; Casas-Saucedo, Rocío; Ruano-Zaragoza, María; Rius, Josefina; Torradeflot, Maria; Bartra, Joan; Munoz-Cano, Rosa; Pascal, Mariona (Frontiers in Allergy, 2022)
Many clinical lab settings still use 0.35kUA/L as the cut-off for serum sIgE immunoassays, while the detection limit is 0.1kUA/L. Clinical relevance of low level sIgE (0.1-0.35kUA/L) remains controversial. Pru p 3 sIgE is considered the main routine tool for assessing Lipid transfer protein (LTP) sensitization. We aimed to evaluate the clinical relevance of Pru p 3 sIgE low levels in a population diagnosed of LTP allergy. Adults diagnosed of LTP allergy and Pru p 3 sIgE ≥0.1kUA/L between 2012-2019 were included. Clinical data was reviewed. nPru p 3 Basophil activation test (BAT) was performed and Basophil Reactivity (BR) and sensitivity (BS) correlated with peach allergy symptoms. Pru p 3 sIgE from 496 subjects was recorded, 114 (23.0%) between 0.1-0.34 kUA/L (grLOW), the rest ≥0.35kUA/L (grB). 44.7% in grLOW and 59.9% in grB were allergic. Urticaria was more frequent in grLOW. In grLOW, Pru p 3 sIgE was higher in patients with local compared to systemic symptoms. In grB, Pru p 3 sIgE was higher in allergic patients. Pru p 3/Total IgE ratios were higher in allergic versus tolerant in both groups. In BAT, BR was similar in both groups. In grLOW, it was higher on allergic compared to tolerant (p=0.0286), and on those having systemic versus local symptoms (p=0.0286). BS showed no significant difference between groups. Although patients with low levels represent a minority, around 45% are peach allergic. BAT showed functional sIgE in them. Pru p 3 sensitization should be carefully evaluated even when sIgE levels are low.